2021
DOI: 10.51470/plantarchives.2021.v21.s1.194
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diarrheagenic E. Coli Among Children Under ‎‏5‏‎ Year’s Age in Tikrit City of Iraq by Using Single Multiplex PCR ‎technique

Abstract: A variety of diarrheagenic E coli (DEC) are responsible for causing diarrhea in children under five years age especially in developing courtiers. The aim of this study was to isolate and bacteriological characterizing of DEC from diarrheic children's stool and using molecular identification of DEC pathotypes for better discrimination and investigate their antibiotic resistance patterns. Total of 200 fresh stools specimens were collected from children with diarrhea in Salah Aldin Hospital in Tikrit city, Iraq. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
0
2
Order By: Relevance
“…In this study, the proportion of EAEC was found to be 10.3%, which contradicts findings in Nigeria [77], China [78], and Qatar [79]. However, these findings are close to the proportions (3.8%) and (6.5%) reported by Mabika et al [50] in Gabon and Shatub et al [51] in Iraq. The disparity in EAEC prevalence reported in these studies may be due to differences in sample types and geographical areas.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In this study, the proportion of EAEC was found to be 10.3%, which contradicts findings in Nigeria [77], China [78], and Qatar [79]. However, these findings are close to the proportions (3.8%) and (6.5%) reported by Mabika et al [50] in Gabon and Shatub et al [51] in Iraq. The disparity in EAEC prevalence reported in these studies may be due to differences in sample types and geographical areas.…”
Section: Discussioncontrasting
confidence: 93%
“…The proportion of DEC detected in this study was higher than the 20.6% to 36.4% reported from Iran [ 47 ], Kenya [ 48 ], and Egypt [ 49 ]. A similar finding with a higher frequency of pathogenic E. coli was documented in Nigeria [ 46 ], Gabon [ 50 ], Iraq [ 51 ], Guinea Bissau [ 52 ], and Sudan [ 53 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation